Forage Fact Sheet Trichanthera - Trinidad and Tobago Goat and Sheep Society, Chaguanas (Trinidad and Tobago) (TTGSS) (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2017)
Brief explanation of the Trichantera: plant description, forage management, cultivation, cutting, transplanting, fertilization and use